OCT4 Positive Cancer Stem Cell Population in Oral Carcinogenesis - Varun Raghavan Pillai; Prathiba Ramani; Jayanthi Palani (Wolters Kluwer Medknow Publications, 2023)
Introduction: Oral squamous cell carcinoma (OSCC) is the predominant histological subtype of oral cancer, which is the sixth most common malignancy worldwide. Despite the advances in therapy, the overall survival rate of oral cancer ranges between 45% and 50%. Cancer stem cells (CSCs) are a small subset of cancer cells that are believed to contribute to local recurrence and therapeutic resistance in OSCC. Cancer stem cells in OSCC express many of the same proteins involved in the core network that regulates embryonic stem cells (ESCs) such as NANOG, OCT4, and SOX2. Octomer binding transcription factor 4 (OCT4) is considered to be one of the major regulators for self-renewal and the maintenance of the stem cell population in the undifferentiated tissue. This study was done to evaluate the expression for OCT4 in OSCC and oral epithelial dysplasia (OED) using immunohistochemistry. Materials and Methods: Histologically proven 40 cases of OSCC, 40 cases of oral leukoplakia with epithelial dysplasia, and 25 cases of normal oral mucosa (NOM) were assessed for immunohistochemical expression of OCT4. The percentage positivity and mean expression of OCT4 were calculated. The final immunohistochemical score was obtained by adding the mean expression and staining intensity of OCT4. Results: The mean expression of OCT4 in OSCC, OED, and NOM was 3.85± 1.05, 8.64± 2.12, and 1.75± 0.23 and the difference was statistically significant (P < 0.01). A higher expression score of OCT4 was observed in 8% and 12% of OSCC and OED, respectively. Conclusion: The higher expression of OCT4 in OSCC and OED suggests that in addition to playing a role in tumorigenesis, OCT4 might be a potential marker for malignant transformation in OED.